Cardiovascular Risk Associated with Methotrexate versus Retinoids in Patients with Psoriasis: A Nationwide Taiwanese Cohort Study - Tsai MH; Chan TC; Lee MS; Lai MS (Clinical Epidemiology, 2021)
Ming-Hsueh Tsai,1 Tom C Chan,2 Meng-Sui Lee,3,4 Mei-Shu Lai5 1Department of Internal Medicine, Taipei City Hospital, Taipei, Taiwan; 2Department of Dermatology, National Taiwan University Hospital and College of Medicine, Taipei, Taiwan; 3Department of Dermatology, Taipei City Hospital, Taipei, Taiwan; 4Faculty of Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 5Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, TaiwanCorrespondence: Meng-Sui LeeDepartment of Dermatology, Taipei City Hospital, No. 33, Sec. 2, Zhonghua Road, Taipei, 100, TaiwanTel/Fax +886 2 23889595 Ext 2225Email leemengsui@hotmail.comMei-Shu LaiInstitute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, 5Fl. No. 17, Hsu Chow Road, Taipei, 100, TaiwanTel +886 2 33668018Email mslai@ntu.edu.twPurpose: Psoriasis is an inflammatory disease associated with cardiovascular disease. Methotrexate (MTX) is a first-line systemic anti-psoriatic agent that may also protect against cardiovascular disease. We examined the cardiovascular risks among patients with psoriasis who were receiving MTX or the comparator, retinoids.Patients and Methods: We analysed data from the Taiwanese National Health Insurance database. The primary outcome was a composite of hospitalisation for ischaemic heart disease, ischaemic stroke and all-cause mortality (composite cardiovascular outcome). Propensity score-weighted analyses were used to evaluate patients who were followed from therapy initiation to the earliest instance of outcome occurrence, insurance disenrollment, death or study termination.Results: We identified 13,777 patients who received MTX and 6020 patients who received retinoids from 2000 to 2012. Compared to retinoids, MTX was associated with lower crude incidences of cardiovascular outcomes, hospitalisation for ischaemic heart disease, ischaemic stroke and all-cause mortality. In intention-to-treat analyses, MTX was associated with lower risks of composite cardiovascular outcomes (adjusted hazard ratio [HR]: 0.84, 95% confidence interval [CI]: 0.76– 0.94), ischaemic heart disease (HR: 0.87, 95% CI: 0.71– 1.06), ischaemic stroke (HR: 1.06, 95% CI: 0.89– 1.27) and all-cause mortality (HR: 0.75, 95% CI: 0.66– 0.85). Similar results were found in as-treated analyses.Conclusion: In this nationwide cohort of patients with psoriasis, compared to retinoids, MTX was associated with a modestly lower risk of cardiovascular events.Keywords: cardiovascular events, inflammation, psoriasis, pharmacoepidemiology